Federalismo e pandemia: a “jurisprudência de crise” do Supremo Tribunal Federal - César Junior, Euclides (2022)
The present work aims to provide subsidies to analyze the jurisprudence of the Supremo Tribunal Federal in disputes between federal entities in the context of the covid-19 pandemic (between February 2020 and June 2021). To this end, conceptual aspects about the intertwining of politics and law at the Court are exposed, as well as the history and legal doctrine of federalism, in order to delimit it as one of the objects of study of the present work, especially the way federalism is incorporated into the formulation of the brazilian Sistema Único de Saúde (Unified Health System). It seeks to find a paradigm of decision in the Federal Supreme Court regarding the dissents involving federal competences before the pandemic and, from this paradigm, analyze the decisions rendered during the crisis caused by the covid-19 pandemic. The approach is justified by the politicization that involved the formulation of public policies to contain the damage caused by the disease, which may (or may not) have influenced the decisions of the Supreme Court in the period. The methodology used is bibliographical research through the analysis of books, legal articles, international documents, legislation, and jurisprudence. The research is pure and qualitative in nature, with descriptive and exploratory purposes.